PEMBINAAN SULUKAN, DHODHOGAN, DAN KOMBANGAN GENDING IRINGAN PAKELIRAN DI PADEPOKAN SENI SAROTAMA SEBAGAI UPAYA PENINGKATAN UNSUR IRINGAN PAKELIRAN - M. Randyo (Institut Seni Indonesia Surakarta, 2016)
A studio as a media of gaining knowledge and arts training as well as practicing needs a serious care because the young generation’s attention towards traditional arts, especially puppetry , today, is decreasing. Studio Sarotama is one of the existing studios which gives dance, karawitan (Javanese traditional music), and puppetry training. Studio Sarotama has existed for about 15 years up to 2010 with about 16 up to 20 students concentrating on dance, karawitan, and puppetry. They study in yunior as well as senior high school. The studio’s achievement needs to be increased by developing through Pengabdian Pada Masyarakat (dedication to society). This is supposed to give knowledge and/or practice in puppetry especially accompaniment. The aim will be catched by appreciation, discussion, and demonstration. Based on the method used, it can be seen that the students are able to manage materials of sulukan, dhodhogan and keprakan in accordance to the performance. The performance that is accompanied includes the scenes of paseban jawi, continued by budhalan wadya and jaranan. Dhodhogan and keprakan are covering keprakan kiprah of puppet, dhodhogan sirep gendhing, keprakan sisiran, and gejogan. The scene of abur-aburan Gathutkaca uses sulukan, ada-ada, palaran and sisiran keprakan, dhodhogan to start accompaniment, and dhodhogan geteran for ada-ada. The scene of war includes the war of Susarma and Abilawa, Rajamala and Abilawa, the scene of perang gagal and perang kembang which mostly use keprakan for example: gejogan, sisiran, platukan, cecrekan.Key words : studio, art, puppetry, accompaniment.